2018
DOI: 10.1158/1541-7786.mcr-17-0362
|View full text |Cite
|
Sign up to set email alerts
|

TANKYRASE Inhibition Enhances the Antiproliferative Effect of PI3K and EGFR Inhibition, Mutually Affecting β-CATENIN and AKT Signaling in Colorectal Cancer

Abstract: Overactivation of the WNT/β-CATENIN signaling axis is a common denominator in colorectal cancer. Currently, there is no available WNT inhibitor in clinical practice. Although TANKYRASE (TNKS) inhibitors have been proposed as promising candidates, there are many colorectal cancer models that do not respond positively to TNKS inhibition and Therefore, a combinatorial therapeutic approach combining a TNKS inhibitor (G007-LK) with PI3K (BKM120) and EGFR (erlotinib) inhibitors in colorectal cancer was investigated.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 47 publications
7
62
0
Order By: Relevance
“…PI3K inhibition promotes the expression of Wnt ligands in breast cancers, whereas BRAF inhibition upregulates b-catenin signaling through activating the focal adhesion kinase in colorectal cancer. Blocking Wnt/b-catenin signaling by tankyrase inhibitor or PORCN inhibitor can significantly enhance the tumor suppression effect of these small molecular inhibitors targeting the growth factor signaling pathways (Tzeng et al, 2015;Solzak et al, 2017;Chen et al, 2018;Solberg et al, 2018). In EGFRmutated lung cancer, even though EGFR inhibitors are not observed to significantly upregulate Wnt signaling in preclinical studies, Wnt/b-catenin signaling has been shown to drive resistance to EGFR inhibitors in lung cancer cells because tankyrase inhibitor and EGFR inhibitor in combination can synergistically suppress lung cancer cell growth in vitro and in vivo (Casás-Selves et al, 2012;Scarborough et al, 2017).…”
Section: Downloaded Frommentioning
confidence: 99%
“…PI3K inhibition promotes the expression of Wnt ligands in breast cancers, whereas BRAF inhibition upregulates b-catenin signaling through activating the focal adhesion kinase in colorectal cancer. Blocking Wnt/b-catenin signaling by tankyrase inhibitor or PORCN inhibitor can significantly enhance the tumor suppression effect of these small molecular inhibitors targeting the growth factor signaling pathways (Tzeng et al, 2015;Solzak et al, 2017;Chen et al, 2018;Solberg et al, 2018). In EGFRmutated lung cancer, even though EGFR inhibitors are not observed to significantly upregulate Wnt signaling in preclinical studies, Wnt/b-catenin signaling has been shown to drive resistance to EGFR inhibitors in lung cancer cells because tankyrase inhibitor and EGFR inhibitor in combination can synergistically suppress lung cancer cell growth in vitro and in vivo (Casás-Selves et al, 2012;Scarborough et al, 2017).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Currently, there are no therapeutic strategies available for targeting WNT/β-catenin signaling to counteract checkpoint inhibitor resistance in melanoma. Here we report that a specific small-molecule tankyrase inhibitor, G007-LK [7][8][9] , attenuates WNT/β-catenin and YAP signaling pathways in the syngeneic murine B16-F10 melanoma model enabling sensitivity to anti-PD-1 immune checkpoint therapy. RNA sequencing of 18 tankyrase inhibitor-treated human melanoma cell lines and B16-F10 cells revealed a transcriptional response profile for a subpopulation.…”
mentioning
confidence: 94%
“…Checkpoint inhibitor treatment, including blockade of the PD-1 receptor, has shown limited efficacy against B16-F10 tumors despite strong expression of the ligand PD-L1 on the tumor cells 10 , a feature attributed to low infiltration by effector CD8 + T cells 11,12 . G007-LK [7][8][9] is a potent and specific tankyrase inhibitor that obstructs WNT/β-catenin and YAP signaling through stabilization of the AXIN-based degradosome and AMOT proteins, respectively 8,[13][14][15][16][17] .…”
mentioning
confidence: 99%
“…Checkpoint inhibitor treatment, including blockade of the PD-1 receptor, has shown limited efficacy in the murine B16-F10 melanoma model, despite strong expression of the ligand PD-L1 on the tumor cells 32 ; a feature attributed to low tumor infiltration by effector CD8 + T cells 33,34 . G007-LK is a potent preclinical stage tankyrase inhibitor with a high selectivity towards tankyrase 1 and 2 and a favorable pharmacokinetic profile in mice with an oral bioavailability of 76% and a t 1/2 of 2.6 hours in female mice 23,35,36 .…”
mentioning
confidence: 99%